ACCEPTANCE ANALYSIS OF USING JD.ID ECOMMERCE APPLICATION WITH TAM METHOD - Saripudin Saripudin; Suharyanto Suharyanto (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
Technological developments, especially in the field of e-commerce such as JD.ID provide convenience and benefits for users. The presence of this application is interesting because it strengthens the brand with guaranteed original products. This study aims to examine the effect of the perceived ease of use variable, whether perceived usefulness has an effect on the use of the JD.ID application with the basic theory of Technology Acceptance Model (TAM). This research is a type of quantitative research conducted by survey. The data collection technique used in this study was a questionnaire (questionnaire) which was distributed online. The sample of this research is the application users. The population in this study amounted to 100 respondents. The sampling technique used was an online questionnaire, the method used was purpose sampling. Data processing method with Smart PLS 3 application. From the test results, it can be seen that perceived ease of use, perceived usefulness have a positive and significant effect on application use. From these results, it means that the higher the perceived ease and usefulness of consumers, the higher the use of the application. The results of this study are in line with the Technology Acceptance Model (TAM) theory.